Factual Conditions Understanding The Ethics of Using Social Media for Secondary School Students in West Java - Kailani, Rizal; Ali, Mohammad; Dewi, Laksmi (Graduate School of Universitas Negeri Malang, 2024)
This research aims to examine the factual conditions of understanding the ethics of using social media by secondary school students in West Java because the use of social media among students currently causes many violations, especially cyberbullying. This study uses a quantitative approach. The research design used was a survey. The research population includes all secondary school students in West Java, with a population of 1015 students. The sample in this study was taken using multistage random sampling. Based on this sampling technique, 446 male and 575 female students were obtained as research samples, with details of 361 grade 10 students, 480 grade 11 students, and 174 grade 12 students. The study results showed that students understand the ethics of using social media in secondary schools in West Java. However, there are problems in other conditions that show that students often violate the ethics of using social media, such as spreading incorrect information, hate speech, and cyberbullying. Digital ethics, which includes seven elements in the use of social media, is essential and necessary to be integrated into the curriculum to support students use of digital technology, especially social media so that students’ good understanding can be strengthened and implemented well.